Real tax reform : replacing the income tax - Makin, John H.; American Enterprise Institute for Public Policy Research (Washington, D.C. : American Enterprise Institute for Public Policy Research, 1985)
The volume develops the case for replacing the United States income tax system with a Bradford X tax and addresses how to design the tax. The authors also counsel about issues in individual and corporate taxation, sought by Democrats and Republicans alike; and also addresses reform options within the income tax system.
Bibliography: p. 39-42.
oo 11/04/2019
Loans
Keywords: Income tax; Spendings tax